Market Dynamics of Allocating Land to Biofuel and Forest Sinks - Korobeinikova, A.; Read, P.; Lermit, J.; Parshotam, A.; Kathirgamanathan, P. (My University, 2001)
Large scale use of biofuel, that is fuel derived from biological materials, especially in combination with reforestation of big areas, can lead to low cost reduction of atmospheric carbon dioxide level. In this paper a model of three markets — fuel, wood products and land — is considered with the aim to evaluate the impact of large scale biofuel production and forestry on the markets and to estimate the cost of a policy aimed at the reduction of the carbon content in the atmosphere. It is shown that the cost is lower than has been expected previously.
Keywords: Kyoto Protocol; Biofuel; Carbon sequestration